Epigenetic alteration of microRNAs in feces of colorectal cancer and its clinical significance. (September 2011) - Cho, William CS
Evaluation of: Kalimutho M, Di Cecilla S, Del Vecchio Blanco G et al. Epigenetically silenced miR-34b/c as a novel faecal-based screening marker for colorectal cancer. Br. J. Cancer 104(11), 1770–1778 (2011). MicroRNAs regulate target gene expression through translation repression or mRNA decay, and they are emerging as important modulators in cellular pathways. Previous studies have shown the occurrence of epigenetically modified miRNAs in colorectal cancer (CRC), identifying these miRNA methylation signatures may provide candidate markers for the detection of malignant colonocytes. Fecal-based tests are widely adopted as noninvasive methods for CRC diagnosis, thus several studies have attempted to use miRNAs from feces as CRC markers. This article evaluates a recently published study investigating the usefulness of epigenetically silenced miRNAs in fecal specimens, including miR-34b/c and miR-148a, as potential markers for CRC screening and prognosis.